Acute Febrile Illness Among Children in Butajira, South–Central Ethiopia During the Typhoid Fever Surveillance in Africa Program. (30th October 2019) - Teferi, Mekonnen; Desta, Mulualem; Yeshitela, Biruk; Beyene, Tigist; Cruz Espinoza, Ligia Maria; Im, Justin; Jeon, Hyon Jin; Kim, Jong-Hoon; Konings, Frank; Kwon, Soo Young; Pak, Gi Deok; Park, Jin Kyung; et al.
Abstract: Background: Clearly differentiating causes of fever is challenging where diagnostic capacities are limited, resulting in poor patient management. We investigated acute febrile illness in children aged ≤15 years enrolled at healthcare facilities in Butajira, Ethiopia, during January 2012 to January 2014 for the Typhoid Fever Surveillance in Africa Program. Methods: Blood culture, malaria microscopy, and blood analyses followed by microbiological, biochemical, and antimicrobial susceptibility testing of isolates were performed. We applied a retrospectively developed scheme to classify children as malaria or acute respiratory, gastrointestinal or urinary tract infection, or other febrile infections and syndromes. Incidence rates per 100 000 population derived from the classification scheme and multivariate logistic regression to determine fever predictors were performed. Results: We rarely observed stunting (4/513, 0.8%), underweight (1/513, 0.2%), wasting (1/513, 0.2%), and hospitalization (21/513, 4.1%) among 513 children with mild transient fever and a mean disease severity score of 12 (95% confidence interval [CI], 11–13). Blood cultures yielded 1.6% (8/513) growth of pathogenic agents; microscopy detected 13.5% (69/513) malaria with 20 611/µL blood (95% CI, 15 352–25 870) mean parasite density. Incidences were generally higher in children aged ≤5 years than >5 to ≤15 years; annual incidences in young children were 301.3 (95% CI, 269.2–337.2) for malaria and 1860.1 (95% CI, 1778.0–1946.0) for acute respiratory and 379.9 (95% CI, 343.6–420.0) for gastrointestinal tract infections. Conclusions: We could not detect the etiological agents in all febrile children. Our findings may prompt further investigations and the reconsideration of policies and frameworks for the management of acute febrile illness.